2019
DOI: 10.1136/bmjopen-2019-029502
|View full text |Cite
|
Sign up to set email alerts
|

Incidental findings on brain imaging and blood tests: results from the first phase of Insight 46, a prospective observational substudy of the 1946 British birth cohort

Abstract: ObjectiveTo summarise the incidental findings detected on brain imaging and blood tests during the first wave of data collection for the Insight 46 study.DesignProspective observational sub-study of a birth cohort.SettingSingle-day assessment at a research centre in London, UK.Participants502 individuals were recruited from the MRC National Survey of Health and Development (NSHD), the 1946 British birth cohort, based on pre-specified eligibility criteria; mean age was 70.7 (SD: 0.7) and 49% were female.Outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…or Level 3 findings might offer a more accurate comparison between our study and the relevant literature conducted in a predominantly non-Latino White and relatively older age cohorts. Within this context, the rates of incidental findings in our Hispanic/Latino population are within or at the upper range of what was previously reported: 2.4% prevalence of chronic infarcts in our study population, compared to 1.2-12.0%; 6,7,9,34,35 1.0% intracranial aneurysms, compared to 0.1-2.3%; 3,4,[6][7][8][9][10][11]31,34,36 0.9% meningiomas, compared to 0.29-2.5%; 3,4,[6][7][8][9]11,34,37,38 0.5% cavernous venous malformations, compared to 0.1-2.4%; [3][4][5][6][7]9,11,31,34,36 0.6% pituitary masses, compared to 0.1-0.8%; [3][4][5][6][7]9,11,34,36 0.5% possible demyelination, compared to 0.04-0.4%; 5,11,31,36 0.2% chronic post-traumatic encephalomalacia, compared to 0.1-0.2%; 31,…”
Section: Follow-upsupporting
confidence: 83%
“…or Level 3 findings might offer a more accurate comparison between our study and the relevant literature conducted in a predominantly non-Latino White and relatively older age cohorts. Within this context, the rates of incidental findings in our Hispanic/Latino population are within or at the upper range of what was previously reported: 2.4% prevalence of chronic infarcts in our study population, compared to 1.2-12.0%; 6,7,9,34,35 1.0% intracranial aneurysms, compared to 0.1-2.3%; 3,4,[6][7][8][9][10][11]31,34,36 0.9% meningiomas, compared to 0.29-2.5%; 3,4,[6][7][8][9]11,34,37,38 0.5% cavernous venous malformations, compared to 0.1-2.4%; [3][4][5][6][7]9,11,31,34,36 0.6% pituitary masses, compared to 0.1-0.8%; [3][4][5][6][7]9,11,34,36 0.5% possible demyelination, compared to 0.04-0.4%; 5,11,31,36 0.2% chronic post-traumatic encephalomalacia, compared to 0.1-0.2%; 31,…”
Section: Follow-upsupporting
confidence: 83%
“…Donors’ motivation to receive additional check-up options as a form of incentive motivation was perceived as predominant by donation organisers. This finding might be ethically challenging given a high chance for receiving incidental findings, especially with particular methods and populations [ 34 ]. In our study, "full check-up" was not perceived as a potential risk by organisers or donors, which might be attributed to the novelty of such practice in Russia.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found a rate of 33.3% in the HIV cohort, 27% in the controls. Such a wide range of prevalence has been hypothesized to be due to varying methods, populations, and sample sizes 9,15,16 . Furthermore, there is evidence that the prevalence of incidental finding detection is more likely using high-resolution MRI sequences 17 .…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Chief among the ethical concerns posed by these findings is the necessity, timing, and context of disclosure to both patients and research participants. Generally, scientific research has followed the fundamental principle of primum non nocere (first, do no harm), as well as general duty to help and rescue 16 . The prevalence of clinically…”
Section: Discussionmentioning
confidence: 99%